2007
DOI: 10.1063/1.2770772
|View full text |Cite
|
Sign up to set email alerts
|

Spatial confinement effects in laser-induced breakdown spectroscopy

Abstract: The spatial confinement effects in laser-induced breakdown of aluminum (Al) targets in air have been investigated both by optical emission spectroscopy and fast photography. A KrF excimer laser was used to produce plasmas from Al targets in air. Al atomic emission lines show an obvious enhancement in the emission intensity when a pair of Al-plate walls were placed to spatially confine the plasma plumes. Images of the Al plasma plumes showed that the plasma plumes evolved into a torus shape and were compressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…27 Plasma properties are found to be highly dependent on the background gas which confines its expansion in the normal and tangential directions. 28,29 In addition, physical confinement of the plasma plume by placing a parallel metallic plate enclosure on the target surface 30 or the generation of plasma plumes inside rectangular cavities 31,32 affect the spatial and temporal distributions of a plasma's properties.…”
mentioning
confidence: 99%
“…27 Plasma properties are found to be highly dependent on the background gas which confines its expansion in the normal and tangential directions. 28,29 In addition, physical confinement of the plasma plume by placing a parallel metallic plate enclosure on the target surface 30 or the generation of plasma plumes inside rectangular cavities 31,32 affect the spatial and temporal distributions of a plasma's properties.…”
mentioning
confidence: 99%
“…Similar focussing/narrowing of the plasma plume in presence of ambient gas has been reported for conventional LPP experiments under different experimental schemes [20][21][22]. Bulgakova et al [22] proposed a most realistic model to explain the focusing (lateral confinement) of laser-produced plasma based on the analogy between an ablated plume and a supersonic under-expanded gaseous jet expanding into the background gas.…”
Section: Resultsmentioning
confidence: 90%
“…These plume narrowing or broadening regimes are both explained in terms of gas scattering effects. Shen et al 12 reported the spatial confinement effects in Al plasma plume between a pair of Al-plate walls, due to the reflection and the compression of the shock wave.…”
Section: Fast Imaging Of Laser-blow-off Plume: Lateral Confinement Inmentioning
confidence: 99%